PROSPECTS FOR MINERAL METABOLIC DISORDERS CORRECTION IN CHILDREN WITH RECURRENT STATE OF URINARY TRACT INFECTION - Budnik, T.V.; Kvashnina, L.V. (World of Medicine and Biology, 2020)
The purpose of the study was to establish the effectiveness of combined phyto-citrate compound in the treatment and prevention of recurrent urinary tract infections in children with saline dysmetabolism in the comparison groups. The study involved 33 children aged 6 to 18 years, patients with recurrent urinary tract infections in the acute exacerbation of the disease. According to the duration of combined phyto-citrate compound administration, children were divided into 2 groups: I (n=17) – received the drug in complex therapy of urinary tract infections for 1 month, II (n=16) – also received phyto-citrate compound in complex therapy for 1 month, but continued to take it to prevent urinary tract infections for the next 2 months in an intermittent mode for 10 days. The results of the study proved phyto-citrate effectiveness in the complex therapy of recurrent urinary tract infections in children on the background of saline dysmetabolism. Administration of this drug led to normalization of saline transport indicators in 82% (27/33) of patients (p
Keywords: recurrent urinary tract infection; children; mineral dysmetabolism; combined phyto-citrate compound